2020
DOI: 10.3389/fbioe.2020.00082
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Bioprinting Causes Ample Alterations of Expression of LUCAT1, IL6, CCL26, and NRN1L Genes and Massive Phosphorylation of Critical Oncogenic Drug Resistance Pathways in Breast Cancer Cells

Abstract: Bioprinting technology merges engineering and biological fields and together, they possess a great translational potential, which can tremendously impact the future of regenerative medicine and drug discovery. However, the molecular effects elicited by thermal inkjet bioprinting in breast cancer cells remains elusive. Previous studies have suggested that bioprinting can be used to model tissues for drug discovery and pharmacology. We report viability, apoptosis, phosphorylation, and RNA sequence analysis of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 95 publications
(103 reference statements)
2
25
0
Order By: Relevance
“…After knocking out LUCAT1 , CRC cell proliferation was significantly inhibited. This is also consistent with the results of studies in cervical cancer, ovarian cancer, breast cancer, choroidal melanoma, clear cell renal cell carcinoma, non-small-cell lung cancer and esophageal squamous cell carcinoma, showing that loss of LUCAT1 hinders cell proliferation 15 , 17 , 20 , 39 , 41 43 . The results described above indicate the oncogenic role of LUCAT1 in CRC.…”
Section: Discussionsupporting
confidence: 91%
“…After knocking out LUCAT1 , CRC cell proliferation was significantly inhibited. This is also consistent with the results of studies in cervical cancer, ovarian cancer, breast cancer, choroidal melanoma, clear cell renal cell carcinoma, non-small-cell lung cancer and esophageal squamous cell carcinoma, showing that loss of LUCAT1 hinders cell proliferation 15 , 17 , 20 , 39 , 41 43 . The results described above indicate the oncogenic role of LUCAT1 in CRC.…”
Section: Discussionsupporting
confidence: 91%
“…[383][384][385] Recently, thermal inkjet printing was also associated with upregulation of oncogenic pathways, increased phosphorylation of kinases and large-scale alternation in gene expression of breast cancer cells. 386 Piezoelectric inkjet printing can also lead to mechanical stress-induced cell death. In particular, printing at high power and/or high vibration frequencies can cause damage to the cell membranes.…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…This offers promise for developing and screening personalized tumor anti-lymphangiogenic therapies in the future. Recent investigation suggested that the gene alterations during bioprinting are evident demonstrated by changes in the expression of LUCAT1, IL6, CCL26, and NRN1L genes and phosphorylation of critical oncogenic drug resistance pathways in breast cancer cells in thermal bioprinted constructs [135] . Understanding such changes at the molecular level in bioprinted constructs would help to develop models that mimic human tumor tissues.…”
Section: Cancer-specific Bioprinted Models For Precision Chemotherapymentioning
confidence: 99%